Organizational Culture Transformation Work From Home (WFH) in Cross-View Generation - Oman Sukmana; Euis Komalawati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2023)
The COVID-19 pandemic that occurred in Indonesia from 2019 to 2022 gave birth to a new organizational culture in the form of work-from-home (WFH) activities to reduce public mobility and reduce the risk of transmission of the COVID-19 virus. After the COVID-19 pandemic, the WFH work culture is still applied in several institutions. This research aims to describe cross-generational views, namely those of the Baby Boomer Generation, Generation X, and Generations Y and Z, regarding the implementation of WFH work culture in the post-pandemic COVID-19 era associated with organizational culture transformation. This research uses a descriptive-qualitative approach through data collection methods such as interviews, observations, and literature studies. The results illustrate that generations have different views on the implementation of work-from-home culture in the post-pandemic COVID-19 era as seen from organizational communication through informative, regulative, persuasive, and integrative functions. The Baby Boomer Generation views the implementation of WFH in the post-pandemic era as an obstacle to organizational communication. Meanwhile, Generation X sees the implementation of WFH as a necessity that cannot be avoided. Although, in some ways, Generation X also still sees the need for face-to-face meetings, Generations Y and Z are the antithesis of the Baby Boomer Generation. Generations Y and Z see the implementation of WFH as not an obstacle to organizational communication.